Implications of Geopolitics in International Diplomacy - Gautam, Gunanath (HISAN: Journal of History Association of Nepal, 2022)
Almost all the nations in the world by virtue of their sovereignty, independence and feeling of nationalism tend to capitalize their potentialities for the benefits of their nations, citizens, economy and boost up production and power in the global context, respecting the territorial integrity and independence for the co-existence and sustainability. Each nation at the utmost level ponders over their wellbeing of its people and hegemony in the international political trauma either for economic, political, social, political or commercial gains. The Russia-Ukraine conflict and the doomed relation that developed between China and Taiwan in the international relationship is the dirty politics engraving the international peace and prosperity in the world. The foul game played by the power-hungry nations to the dominated and weak nations ate internationally condemned which is against the international laws in diplomatic procedure.